Caring as sustainable coaching in elite athletics: benefits and challenges - Dohsten, J.; Barker-Ruchti, N.; Lindgren, E. C. (Sports Coaching Review, 2020)
Coaches in elite sport must ensure a balance between performance, high pressure and well-being. A caring approach, based on a coach`s commitment to caring for athletes, has the potential to create such a balance and sustainability. The aim of this study was to identify coaches` caring and problematise their ethics of care in relation to sustainability. We draw on and integrate the theoretical concept of caring into a conception of (un-) sustainable sport. Semi-structured interviews were conducted with seven Swedish elite athletics coaches. Results show that coaches` ethics of care is important for creating sustainable elite athletics practices, but that caring also conflicts with sustainability thinking if coaches do not base their actions on practical wisdom and moral and ethical dilemmas.